Two Isoforms of serpent Containing Either One or Two GATA Zinc Fingers Provide Functional Diversity During Drosophila Development - Moussalem, Douaa; Augé, Benoit; Di Stefano, Luisa; Osman, Dani; Gobert, Vanessa; Haenlin, Marc (Frontiers in Cell and Developmental Biology, 2022)
GATA transcription factors play crucial roles in various developmental processes in organisms ranging from flies to humans. In mammals, GATA factors are characterized by the presence of two highly conserved domains, the N-terminal (N-ZnF) and the C-terminal (C-ZnF) zinc fingers. The Drosophila GATA factor Serpent (Srp) is produced in different isoforms that contains either both N-ZnF and C-ZnF (SrpNC) or only the C-ZnF (SrpC). Here, we investigated the functional roles ensured by each of these isoforms during Drosophila development. Using the CRISPR/Cas9 technique, we generated new mutant fly lines deleted for one (ΔsrpNC) or the other (ΔsrpC) isoform, and a third one with a single point mutation in the N-ZnF that alters its interaction with its cofactor, the Drosophila FOG homolog U-shaped (Ush). Analysis of these mutants revealed that the Srp zinc fingers are differentially required for Srp to fulfill its functions. While SrpC is essential for embryo to adult viability, SrpNC, which is the closest conserved isoform to that of vertebrates, is not. However, to ensure its specific functions in larval hematopoiesis and fertility, Srp requires the presence of both N- and C-ZnF (SrpNC) and interaction with its cofactor Ush. Our results also reveal that in vivo the presence of N-ZnF restricts rather than extends the ability of GATA factors to regulate the repertoire of C-ZnF bound target genes